Religious and Social Aspects of Kuka Movement: The Kuka Movement: A Catalyst for Social and Religious Reforms in Colonial India (Journal of Advances and Scholarly Researches in Allied Education, 2015)
Religiously and socially, the condition of the land of the five rivers, as well as the rest of India was not better. It was in the above social and religious circumstances that Kukaism was initiated in order to drive away, to accuse social weakness, to meet the challenge of an overpowering western imperialism, and to fabricate the bonds of religious purity and brotherhood. It represented social reforms, clean living, honest earning, equality and simplicity when people in the Punjab had forgotten the message of Guru Nanak and Guru Gobind Singh. The work of the movement should not be under estimated. They created a reawakening in the land. They were the leaders which set the country on the path of progress, whereas the other movements devoted themselves entirely to social and religious movement but harsh behaviour of the British Government with the leaders of this movement, draw them into political sphere also.